2002
DOI: 10.1210/jcem.87.8.8767
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Peculiar Mutation in the Sodium/Iodide Symporter Gene in Spanish Siblings with Iodide Transport Defect

Abstract: Previously, we reported two Spanish siblings with congenital hypothyroidism due to total failure of iodide transport. These were the only cases reported to date who received long-term iodide treatment over 10 yr. We examined the sodium/iodide symporter (NIS) gene of these patients. A large deletion was observed by long and accurate PCR using primers derived from introns 2 and 7 of the NIS gene. PCR-direct sequencing revealed a deletion of 6192 bases spanning from exon 3 to intron 7 and an inverted insertion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
0
19
0
2
Order By: Relevance
“…The resulting impairment in I − uptake in the thyroid leads to congenital hypothyroidism, which, unless treated early in life by TH administration, causes goiter and even mental retardation. Study of the 14 ITD-causing NIS mutations identified to date (27)(28)(29)(30)(31)(32)(33)(34)(35)(36) has been instrumental in the identification of residues key for NIS transport activity (5, 16, 17, 22-25, 37, 38). For example, the analysis of T354P revealed the role in NIS function of TMS9, where this mutation is located (23).…”
Section: Significancementioning
confidence: 99%
“…The resulting impairment in I − uptake in the thyroid leads to congenital hypothyroidism, which, unless treated early in life by TH administration, causes goiter and even mental retardation. Study of the 14 ITD-causing NIS mutations identified to date (27)(28)(29)(30)(31)(32)(33)(34)(35)(36) has been instrumental in the identification of residues key for NIS transport activity (5, 16, 17, 22-25, 37, 38). For example, the analysis of T354P revealed the role in NIS function of TMS9, where this mutation is located (23).…”
Section: Significancementioning
confidence: 99%
“…3 in Kornreich et al [1990]), RB1 (see Fig. 4 in Greger et al [1990]), and SLC5A5 (MIM] 601843 [Kosugi et al, 2002]). In these genes the inserted sequence constitutes an internal portion of the removed sequence, but in inverted orientation.…”
Section: Inversions That Involve the Partial Reinsertion Of The Removmentioning
confidence: 99%
“…The presence of charged residues (of any polarity) other than Glu at position 267 rendered NIS inactive without affecting its expression or targeting, but substitution with neutral residues at this position was compatible with partial activity. Pohlenz et al, 1998;Kosugi et al, 1999;Kosugi et al, 2002;Levy et al, 1998c) (Fig. 1A).…”
mentioning
confidence: 95%